2016
DOI: 10.1002/anie.201607036
|View full text |Cite
|
Sign up to set email alerts
|

Probing Functional Heteromeric Chemokine Protein–Protein Interactions through Conformation‐Assisted Oxime Ligation

Abstract: Protein–protein interactions (PPIs) govern most processes in living cells. Current drug development strategies are aimed at disrupting or stabilizing PPIs, which require a thorough understanding of PPI mechanisms. Examples of such PPIs are heteromeric chemokine interactions that are potentially involved in pathological disorders such as cancer, atherosclerosis, and HIV. It remains unclear whether this functional modulation is mediated by heterodimer formation or by the additive effects of mixed chemokines on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…In this regard, chemokine heterodimerization can modulate the overall signaling response of GPCRs, thereby providing a general mechanism for regulating chemokine function. The recent synthesis and in vitro / in vivo testing of a covalently-linked CXCL4/CCL5 heterodimer has validated the functional relevance of chemokine heterodimers in GPCR-mediated signal transduction [ 42 , 89 ].…”
Section: Functional Impact Of Chemokine Structurementioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, chemokine heterodimerization can modulate the overall signaling response of GPCRs, thereby providing a general mechanism for regulating chemokine function. The recent synthesis and in vitro / in vivo testing of a covalently-linked CXCL4/CCL5 heterodimer has validated the functional relevance of chemokine heterodimers in GPCR-mediated signal transduction [ 42 , 89 ].…”
Section: Functional Impact Of Chemokine Structurementioning
confidence: 99%
“…Based on these studies, other chemokine-derived peptides were designed and shown to be effective chemokine antagonists [ 42 ]. However, it was the design and synthesis of a covalently-linked CXCL4/CCL5 heterodimer [ 89 ] that has provided the most compelling evidence in vitro and in vivo it validated the biological relevance of chemokine heterodimers [ 42 ]. These studies may contribute to the development and promise of novel chemokine antagonists for use in the clinic.…”
Section: Chemokine Antagonistsmentioning
confidence: 99%
“…[47] Tilman Hackeng (CardiovascularR esearch Institute Maastricht/Maastricht University,T he Netherlands) discussed recent applicationso fo xime ligation reactions to probe functional heteromeric chemokinep rotein-protein interactions. [48] He furthermorer eporteda no xime ligationr eaction that can be accelerated under aqueous conditions, at low concentrationsa nd at neutral pH by freezing. [49] Phil Dawson (The Scripps Research Institute,U SA) described how as mall combinatorial peptidelibrary can be built through sequential click reactions starting from as ingle parent peptide.…”
Section: Protein Synthesis Beyond the Ribosome: Advances In Chemical mentioning
confidence: 99%
“…To explore different medical and biotechnological applications, biomolecules (such as peptides, DNA, and antibodies) as well as small molecules (dyes, radioisotopes, MRI contrast agents, drugs) were coupled in a precise manner to proteins of interest . Tilman Hackeng (Cardiovascular Research Institute Maastricht/Maastricht University, The Netherlands) discussed recent applications of oxime ligation reactions to probe functional heteromeric chemokine protein–protein interactions . He furthermore reported an oxime ligation reaction that can be accelerated under aqueous conditions, at low concentrations and at neutral pH by freezing .…”
Section: Peptide/protein Labeling and Bioorthogonal Chemistries To Mamentioning
confidence: 99%
“…1,2 Hydrazone and oxime formation show useful reaction rates at mildly acidic pH (4-5) but are very slow processes in water at neutral pH, which is the preferred media for manipulating complex biomolecules such as proteins. As a consequence, many studies focused on accelerating these reactions by thermal activation, 3 by freezing, 4 by protein-protein complex formation, 5 by addition of organic co-solvents 3 or catalysts. 1,[6][7][8][9] Nucleophilic catalysis by amine compounds such as aniline 6,8 (or derivatives thereof 10,11 ) or N,N-dimethylaminoethylamine 7,12 has proven especially powerful in this regard (Figure 1).…”
mentioning
confidence: 99%